Electrochemical Phosphorylation of Organic Molecules. Issue 12 (5th October 2020) - Sbei, Najoua; Martins, Guilherme M.; Shirinfar, Bahareh; Ahmed, Nisar
Abstract: Organophosphorus chemistry is a broad field with multi‐dimensional applications in research area of organic, biology, drug design and agrochemicals. Conventional methods have been adopted extensively to access phosphorylated compounds that rely on the use of toxic, moisture sensitive phosphorylating agents and occur in the presence of oxidants, catalysts, as well as high temperatures and harsh conditions are required for complete transformations. However, recent progress has been made for phosphorylation reactions using electricity to introduce green and sustainable synthetic procedures. These reactions can be performed at mild conditions and proceed with excellent atom economy. Herein, we targeted electrochemical phosphorylation reactions with generation of new bonds such as C(sp 3 ) −P, C(sp 2 ) −P, O−P, N−P, S−P and Se−P. This review is aimed to offer an overview of recent developments in the synthetic methodology to easy access of organophosphorus compounds using electrochemistry. Abstract : Herein, electrochemical phosphorylation reactions involving catalyst and catalyst‐free conditions, with generation of new bonds such as C(sp 3 )−P, C(sp 2 ) −P, O−P, N−P, S−P and Se−P have been discussed.